2008
DOI: 10.1126/science.1161847
|View full text |Cite
|
Sign up to set email alerts
|

A Physical Map of the 1-Gigabase Bread Wheat Chromosome 3B

Abstract: As the staple food for 35% of the world's population, wheat is one of the most important crop species. To date, sequence-based tools to accelerate wheat improvement are lacking. As part of the international effort to sequence the 17-billion-base-pair hexaploid bread wheat genome (2n = 6x = 42 chromosomes), we constructed a bacterial artificial chromosome (BAC)-based integrated physical map of the largest chromosome, 3B, that alone is 995 megabases. A chromosome-specific BAC library was used to assemble 82% of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
427
0
7

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 367 publications
(443 citation statements)
references
References 23 publications
9
427
0
7
Order By: Relevance
“…It is represented by a minimum tiling path (MTP) of 67,000 BAC clones. Given a genome size of 5.1 Gb 10 , more than 95% of the barley genome is represented in the physical map, comparing favourably to the 1,036 contigs that represent 80% of the 1 Gb wheat chromosome 3B 11 .…”
Section: A Sequence-enriched Barley Physical Mapmentioning
confidence: 99%
“…It is represented by a minimum tiling path (MTP) of 67,000 BAC clones. Given a genome size of 5.1 Gb 10 , more than 95% of the barley genome is represented in the physical map, comparing favourably to the 1,036 contigs that represent 80% of the 1 Gb wheat chromosome 3B 11 .…”
Section: A Sequence-enriched Barley Physical Mapmentioning
confidence: 99%
“…The International Wheat Genome Sequencing Consortium aims at flow-sorting and sequencing the individual chromosomes of bread wheat, and significant progress has been made with several chromosomes, for example 3B (ref. 6) and 4A (ref. 7).…”
mentioning
confidence: 99%
“…Initial studies were based on aneuploid stocks (deletion lines; Endo and Gill 1996) and revealed that the frequency of meiotic recombination is highly biased toward the ends of chromosomes (Paris et al 2000;Paux et al 2008;Saintenac et al 2009). However, this does not rely on the distal position since when the chromosome arms are inverted (telomeres placed at the centromeres and vice versa), COs still occur in the same region whatever its location (Lukaszewski et al 2012).…”
mentioning
confidence: 99%